A replication of "The role of intermediaries in facilitating trade" (Journal of International Economics, 2011) - Jianhua Duan; Qian Xuefeng; Kuntal K. Das; Laura Meriluoto; W. Robert Reed (Kiel Institute for the World Economy (IfW), 2019)
This study replicates Ahn, Khandelwal, and Wei's (AKW 's) (2011) model of intermediary trade. The authors' study produces two main results. First, the authors are able to reproduce empirical evidence for AKW's three main predictions for Chinese exports. This is impressive because much of the data for their replication are independently sourced. However, when they subject AKW's model to additional tests, they find that the evidence is not robust. Using more recently available data to test AKW's first prediction, the authors estimate coefficients that are wrong-signed and significant. When they re-analyze the evidence supporting AKW's second and third predictions, they find that the full sample results mask significant heterogeneity across Chinese regions. In many cases, key coefficients are insignificant. In a few cases, they are wrong-signed and significant. Finally, using multiple versions of a key variable measuring the number of required import documents by country, they discover that the results are not robust across versions.
https://doi.org/10.7910/DVN/BT8JPN
Keywords: F1; 330; intermediaries; exports; productivity; heterogeneous firms; China